A Chromosome-Scale Reference Assembly of a Tibetan Loach, Triplophysa siluroides - Yang, Liandong; Wang, Ying; Wang, Tai; Duan, Shengchang; Dong, Yang; Zhang, Yanping; He, Shunping (Frontiers in Genetics, 2019)
Cobitoidea is one of the two superfamilies in Cypriniformes; however, few genomes have been sequenced for Cobitoidea fishes. Here, we obtained a total of 252.90 Gb of short Illumina reads and 31.60 Gb of long PacBio Sequel reads, representing approximate genome coverage of 256× and 50×, respectively. The final assembled genome is about 583.47 Mb with contig N50 sizes of 2.87 Mb, which accounts for 91.44% of the estimated genome size of 638.07 Mb. Using Hi-C–based chromatin contact maps, 99.31% of the genome assembly was placed into 25 chromosomes, and the N50 is 22.3 Mb. The gene annotation completeness was evaluated by BUSCO, and 2,470 of the 2,586 conserved genes (95.5%) could be found in our assembly. Repetitive elements were calculated to reach 33.08% of the whole genome. Moreover, we identified 25,406 protein-coding genes, of which 92.59% have been functionally annotated. This genome assembly will be a valuable genomic resource to understand the biology of the Tibetan loaches and will also set a stage for comparative analysis of the classification, diversification, and adaptation of fishes in Cobitoidea.